How Individuals’ Activity-Travel Behaviour Shape Human Activity Space - Abdul Khalif, Mohd Zamri (Universiti Teknologi PETRONAS, 2017)
This study examines the nature of the day-to-day variability of individual activity space, different in socio-demographic and built environment can influence human activity space and the land use pattern with the activity space when someone is travel. It focuses on the activity space of people that living in the area of Seri Iskandar, Perak including Universiti Teknologi Petronas. To get the findings, a travel survey need to be designed and conducted where a questionnaire about the respondent characteristic and activity diary need to be fill by the respondent. For the number of respondents, it was agreed that only the data from 143 respondents can be used to analyze. The travel survey has been conducted for five days which are Wednesday until Sunday. After that, the results of the survey need to be input in a computer’s software to ease the analytical computation using multivariate analysis.